The death of the Inca. Two versions of an Ashaninca myth - Fernández, Eduardo (1984)
The Viracochas arise among the Ashanincas due to the disobedience of their father's youngest son, the Inca. They kill the Inca, cutting off his head and taking it to Lima where it never dies and continues talking.